DILEMA TEKNOLOGI DAN KEMELUT KEPERCAYAAN DALAM FIKSI DISTOPIA KARYA RAY BRADBURY (The Dilemma of Technology and Trust Crisis in Dystopia Fiction by Ray Bradbury) - Novita Dewi (Balai Bahasa Sulawesi Selatan, 2020)
In this post-truth era, dystopia fiction is important as empathy, trust, and compassion fall apart. This literary genre predicts a terrible future when people forced to submit to tyrants who control unlimited power in economics, politics, and technology. This study aims to examine two dystopia short stories by Ray Bradbury, i.e. The Pedestrian and All Summer in a Day. These two short stories are placing in the context of contemporary society, which has high technology and ignorant of objective truths since they accept facts built on emotions, opinions, and some particular ideologies. By using content analysis, this study reveals two main findings. First, there is an oscillation of people who worship technology and those who are fearful of technology in both short stories. The diverse characters become further alienated to one another as technology rules over. Second, technology sometimes turns into an enemy that hampers the relationship among the characters; as a result, intolerance swarms when the objective truth sinks in a wave of public opinions, in this case, represented by the voice of the authoritarian government in the first short story, and that of the Venusian pupils in the second story.AbstrakFiksi distopia memberikan sumbangan penting ketika empati, kepercayaan, dan bela rasa berguguran di era pascakebenaran ini. Ragam karya sastra ini meramalkan masa depan yang mengerikan ketika masyarakat dipaksa tunduk pada tiran-tiran yang menguasai ekonomi, politik, dan teknologi tanpa batas. Penelitian ini bertujuan membahas dua cerita pendek distopia karya Ray Bradbury, “The Pedestrian” dan “All Summer in a Day”, dengan menempatkan keduanya dalam konteks masyarakat kontemporer berteknologi tinggi yang abai pada kebenaran objektif karena menerima kebenaran yang dibangun atas emosi, opini, dan ideologi tertentu. Dengan memakai metode analisis konten, penelitian ini menghasilkan dua temuan utama. Pertama, terjadi tarik-ulur antara masyarakat yang memberhalakan teknologi dan yang fobia terhadap teknologi di kedua cerpen tersebut. Tokoh-tokoh cerita makin terasing satu sama lain ketika teknologi berkuasa. Kedua, teknologi kadang menjadi musuh yang menghalangi perjumpaan dan keterhubungan antar tokoh; akibatnya, timbul intoleransi ketika kebenaran objektif kandas oleh opini-opini publik yang dalam hal ini diwakili oleh suara pemerintah yang otoriter pada cerpen yang pertama dan siswa-siswa sekolah di planet Venus pada cerpen yang kedua.